Analysis of the Anthrax Morbidity Rate in the Russian Federation in 2011, and Prognosis for 2012 - A. G. Ryazanova; E. I. Eremenko; E. A. Tsygankova; L. Yu. Aksenova; O. I. Tsygankova; N. P. Buravtseva; T. M. Golovinskaya; A. N. Kulichenko (Проблемы особо опасных инфекций, 2012)
Carried out is the analysis of epidemiological situation on anthrax in 2011, both in the Russian Federation and around the world. The results of the analysis bear evidence of the fact that in the constituent units of the federal districts of Southern Russia and Siberia anthrax morbidity in humans will be retained at the annual average level (characteristic of the recent decade) - ranging from 1 to 20 cases of the disease.